Post adoption behaviour of farmers towards soil and water conservation technologies in watershed management programme - MEENA, R. B.; SINGH, A. K.; MEENA, D. C. (Journal of Soil and Water Conservation, 2020)
Soil and Water Conservation (SWC) programme could be more cost effective if they are based upon the understanding of farmer’s perception about SWC technologies and the conditions under which they adopt and maintain these technologies. In this context, understanding extent of post-adoption behaviour among farmers is crucial in terms of utility of SWC technologies and their further scope of improvement. Therefore, this study was conducted in 2012 at Agra watershed to understanding the post-adoption behaviour (continued-adoption, discontinuance, technological gap, diffusion and infusion) of farmers regarding different adopted SWC technologies of watershed management. The results of this study showed that TCAIs of engineering measures like land levelling, bunding, terracing and grassed waterway were found more than 90 per cent. However, TCAIs of agronomical interventions were zero except summer ploughing and green manuring which was 100 and 6.67 percent, respectively. Extent of post adoption behaviour of farmers regarding continue adoption, dis-adoption and diffusion of SWC technologies were observed 59.55, 40.45, and 34.08 percent, respectively. This was showed moderate adoption level of farmers concerning different soil and water conservation technologies in the watershed. The present study provided scientific information on the important personal and psychological factors or probable reasons responsible for continued-adoption, dis-adoption and technological gap in soil and water conservation technologies adopted in watersheds management programme.